2011
DOI: 10.1177/0892705711412650
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and electrical properties of poly(vinyl chloride) loaded with carbon nanotubes and carbon nanopowder

Abstract: Two groups of polymer nanocomposite samples were synthesized. One of them was Poly(vinyl chloride) (PVC) loaded with different concentrations of carbon nanopowder (CNP), while the other was PVC loaded with different concentrations of carbon nanotubes (CNTs). The dependence of the tensile mechanical parameters, rheological properties and the dc electrical conductivity on the concentration of either filler was investigated. Results revealed a lower electrical and mechanical percolation threshold of CNTs than CNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…In addition, raising T increases r 1 and r 2 , especially for 1 wt% CNT incorporation. Aljaafari et al reported that CNT/PVC composites demonstrated non‐ohmic behavior, whereas Ferrara et al reported ohmic behavior in the range of −10 to 10 V for LLDPE/CNT nanocomposite films. The value of r is used to report the conduction mechanism in polymers .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, raising T increases r 1 and r 2 , especially for 1 wt% CNT incorporation. Aljaafari et al reported that CNT/PVC composites demonstrated non‐ohmic behavior, whereas Ferrara et al reported ohmic behavior in the range of −10 to 10 V for LLDPE/CNT nanocomposite films. The value of r is used to report the conduction mechanism in polymers .…”
Section: Resultsmentioning
confidence: 99%
“…However, homogenous dispersion of CNTs is difficult due to the van der Waals interactions between the CNTS, consequently leading to the formation of agglomerations (Song et al 2013). In this respect, the melt-mixing method is the preferred method of fabricating CNT-filled polyvinyl chloride (Farsheh et al 2011;Aljaafari et al 2012). The MWCNT-filled polyvinyl chloride mixed matrix membrane is suitable for gas separation applications, as well as an indicator electrode in potentiometric titrations (Abu-Abdeen 2012).…”
Section: Cnts: In Polyvinyl Chloride Polymeric Compositesmentioning
confidence: 98%
“…This is due to the high conductivity and the aspect ratio of CNTs (Ma et al 2014a, b). Consequently, the percolation threshold concentration and nanocomposites conductivity determined by polymer type, synthesis technique, aspect ratio of CNTs, the extrication of CNTs agglomerates, uniform spatial distribution of single CNTs and the level of alignment (Aljaafari et al 2012). Another considerable factor, which influenced the electrical conductivity of nanocomposites is the chemical functionalization of CNTs.…”
Section: Semiconductor Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39] However, there is not a unified criterion about the best processing parameters, neither a generalized criterion about the method for preparing the composites. Some authors have demonstrated that the melt mixing dispersion stand out the positive temperature effect in comparison with the solution mixing for CB polymer composites, 40 whereas others 41 have evidenced that processing conditions influence the sensibility detection to organic vapors.…”
Section: Introductionmentioning
confidence: 99%